Proposal to represent the UNESCO thesaurus for the semantic web applying ISO-25964 - PASTOR-SÁNCHEZ, Juan-Antonio (2015)
This paper shows how has been applied ISO-25964 standard to represent the UNESCO thesaurus through semantic web technologies. Based on the works done by the UNESKOS project, has been analyzed the joint use of SKOS and ISO THES ontologies to represent thesauri according to the data model of the ISO-25964 standard. The result has been an RDF dataset, accessible as Linked Open Data, using SKOS and ISO-THES with the properties of a vocabulary developed in the context of UNESKOS project. The conclusions point, among other aspects, a review of SKOS and adoption of appropriate technologies that facilitate the development of future works and research lines focused on the alignment of vocabularies